Transfer of Pyrochroa daglariensis to Hemidendroides Ferrari (Coleoptera: Pyrochroidae: Pyrochroinae), with a dichotomous key to the four species of the genus - Young, Daniel K. (Zootaxa, 2009)
Having discovered a primary homonym associated with the pyrochroid species name Dendroides cyanipennis, Young (2004) reviewed the taxonomic history of the species and proposed the replacement name Pyrochroa daglariensis for the junior homonym. This species was previously known solely from the presumed syntype series of two females from the northeastern part of the Turkish province of Hatay, near the Turkey-Syria boarder in the Nur Dağlari mountains. The generic association with Pyrochroa was made in deference to Blair’s (1914) treatment, although Young (2004: 935) added, “Discovery of males would allow better assessment of important characters such as the cranial pit apparatus and genitalia.”